Segmental clavicle fracture and acromio-clavicular joint disruption: an unusual case report - Marjoram, Tom P (Shoulder Elbow, 2015)
Clavicle fractures are common, accounting for 2.6% of all adult fractures. We describe a most unusual segmental fracture pattern of the clavicle with concurrent disruption of acromioclavicular (AC) joint. We were unable to find any publications or reports describing this fracture pattern. During surgery for a medial one-third shaft of clavicle fracture and AC joint dislocation, the medial clavicle was exposed, leading to the discovery (on table) of a previously unidentified additional undisplaced fracture of the medial clavicle cleaving the bone into three distinct fragments. An anatomical plate was successfully applied, fixing both fractures. The AC joint was then reduced with a hook plate. At 8 months, after removal of the hook plate, the patient has an excellent outcome with an Oxford Shoulder Score of 45/48 and a full range of movement without instability of the AC joint. We describe the operative management of this rare fracture pattern. This also highlights that segmental fractures of the clavicle are easily missed. It was successfully treated with a medial anatomic plate and lateral hook plate. We were unable to find any publications or reports describing the fracture pattern in this case.